Failed innovation implementation in teacher education: A case analysis - Dobozy, Eva (Scientia Educologica, 2012)
The global call for teacher quality improvement and numerous accounts of resistance to education reform at all levels of the education system brings to the forefront the tension between rhetoric and reality. This case study reports on a failed innovation attempt, which was based on the need for a signature pedagogy in Australian teacher education that better prepares beginning teachers for the demands of flexible, student-centred learning design. To assist teacher education students’ development of deep learning engagement, which is a pre-condition for the acquisition of 21st century knowledge, skills and learning attitudes, we need to better understand resistance behaviour. The reported research illustrates how the learning-centric teaching design was unable to engage ‘consumer students’ in deep learning experiences due to heightened negative emotion experienced by a great number of students. The provision of this illustrative practical example of innovation failure has the potential to make apparent how students’ ‘out-of-comfort-zone’ behaviour and resistance to change from transmission education practices to social constructivist approaches will need to be managed.